Cover Feature: Enhancement of Peroxidase Activity in Artificial Mimochrome VI Catalysts through Rational Design (ChemBioChem 17/2018). (13th August 2018) - Caserta, Giorgio; Chino, Marco; Firpo, Vincenzo; Zambrano, Gerardo; Leone, Linda; D'Alonzo, Daniele; Nastri, Flavia; Maglio, Ornella; Pavone, Vincenzo; Lombardi, Angela
Abstract : The cover feature picture shows balls enclosing two artificial heme peroxidases. The cracked crystal ball and the steel ball symbolize the different features of the two molecules. A previous catalyst (FeMC6*), which suffered from bleaching during catalysis, was made more robust and active by inserting 2‐aminoisobutyric acid residues (Aib), thus giving rise to a new molecule (FeMC6*a) with improved catalytic behavior. The Aib residues are painted inside a set of gear wheels to signify their importance for catalyst function and stability. More information can be found in the communication by A. Lombardi et al. on page 1823 in Issue 17, 2018 (DOI: 10.1002/cbic.201800200 ).